2022
DOI: 10.1371/journal.pone.0261717
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Education 4.0 among engineering students for learning English language

Abstract: Education 4.0 is considered a significant technology for teaching and learning. The present study aims to explore the impact and the importance of Education 4.0 for improving English language learning in the perception of students in India, especially Hyderabad City. Moreover, Education 4.0 has bloomed as an important need to move along with the fast-growing education system of the world. But, it is a fact that many Indian students have complications and difficulties in learning English due to many reasons. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 33 publications
1
22
0
Order By: Relevance
“…But besides this, students are fundamentally facing complications and difficulties in their learning. Based on this notion, the study on 145 Indian students revealed a direct correlation between student self-concept (i.e., belief, perception) and student intention of EFL ( 57 , 58 ).…”
Section: Literature Reviewmentioning
confidence: 96%
“…But besides this, students are fundamentally facing complications and difficulties in their learning. Based on this notion, the study on 145 Indian students revealed a direct correlation between student self-concept (i.e., belief, perception) and student intention of EFL ( 57 , 58 ).…”
Section: Literature Reviewmentioning
confidence: 96%
“…During the COVID-19 pandemic, technology-based methods, tools, and materials have got more common in language teaching and learning [25]. Technology allows students to connect with a broad network and developed communication platforms with educators, parents, and stakeholders [26]. With the growth of technology, games have become more essential in the field of language acquisition.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Furthermore, autonomous learners can be identified by specific characteristics, including being methodical and disciplined in their learning, logical and analytical in thinking, reflective and self-aware, and exhibiting persistent curiosity, motivated, flexible, and being proficient in interpersonal and interrelated areas; they have perseverance and are responsible and creative, independent, and selfsufficient [13]. Another fundamental aspect for developing self-sufficient students is to take into consideration the differences among them in order to make learning completely unique for each individual [13,14]. erefore, with the development of autonomy within learners, these differences, such as motivation and learners' abilities and competencies, are no longer a hindrance in the language class.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few decades ago, language learning underwent significant reforms in the communicative approach [14,21].…”
Section: Learner Autonomy and Language Learningmentioning
confidence: 99%